Carlos Ribeiro (1813-1882) e as antas de Belas : um contributo para a história da ciência em Portugal no século XIX - Cardoso, João Luís (2016)
An evaluation of Carlos Ribeiro’s (1813-1882) work regarding the excavation of four dolmens in the outskirts of Belas (Sintra, Portugal) is presented here. These excavations were initiated in 1875 and extended intermittently until 1878. The results were exemplarily published in a monograph in 1880 containing rigorous descriptions of the monuments and its respective findings (portrayed by beautiful charcoal drawings of the tombs and its findings). The quality of graphic recording is accompanied by a discussion regarding the importance of observing: the construction techniques adopted; how the terrain and geologic background conditioned its construction; as well as the type of raw materials used in the making of artifacts and its meaning. Thanks to Carlos Ribeiro’s own manuscript notes it was possible to complement his published work. These notes are comprised of preliminary parts of the published work together with field observations conducted during the excavations. Also, they were intersected with notations from other publications compiled by Carlos Ribeiro which he used in the discussion of his own results. These documents illustrate how based on a scientific method the author built his archaeological discourse, emerging as one of the pinnacles in his field of knowledge in Portugal, together with his colleagues of the Geological Commission, Francisco Pereira da Costa and Joaquim Filipe Nery Delgado. Besides illustrating the production of scientific discourse, based on data collected in the field, and then in the lab until its final result, this paper also provides information regarding the number of field work days and respective participants in the last phase of excavations conducted during most of the Summer of 1878 at the monuments of Monte Abraão, Estria and Carrascal/Agualva.